Analisis Kinerja Ekonomi Desa Pesisir di Kabupaten Batang Tahun 2013–2017 - Surya Arga Purnama; Maruto Umar Basuki (Universitas Diponegoro, 2020)
Coast is a meeting area between land and sea. The development of the coastal areas to improve the community's economy. One of the developments using the Resilient Coastal Village Programs (RCV). Resilient Coastal Village Program (RCV) aims to develop the Human Aspects, Business Aspects, Resources Aspects, Environmental and Infrastructure Aspects, and Disaster Management Aspects. The Resilient Coastal Village Program (RCV) is carried out in 20 coastal villages in Batang City. The purpose of this study to analyze the economic perfomance of coastal villages in Batang city. This study uses secondary data obtained from the Departement of Fisheries, Animal, and Marine in the Batang City. The study uses Klassen Typology Analysis and Descriptive Analysis to analyze the economic perfomance of coastal villages in Batang City. Klassen Typology Analysis was used to classify coastal villages in Batang City. The results of the analysis of the description of aspects in the value of toughness increase every year. The aspects of disaster management and climate change are the lowest aspects of the 4 other aspects in the value analysis of resilience. Klassen's Typology analysis results show that in 2017, coastal villages are divided into quadrant I and quadrant II.